Two cases of polycystic ovary syndrome with onset of severe ovarian hyperstimulation syndrome following controlled ovarian stimulation with aromatase inhibitors for fertility preservation before breast cancer treatment - Sugiko Oishi; Keiko Mekaru; Rie Nakamura; Maho Miyagi; Kozue Akamine; Chiaki Heshiki; Yoichi Aoki (Elsevier, 2021)
Objective: The risks of ovarian hyperstimulation syndrome (OHSS) involve high estrogen (E2) levels. We report two breast cancer patients with polycystic ovarian syndrome who underwent fertility preservation and had severe OHSS; their E2 levels were lowered using aromatase inhibitors (AI). Case Reports: A 36-year-old woman underwent controlled ovarian stimulation (COS) with AI and cryopreserved 10 blastocysts. She was hospitalized with OHSS (E2 = 139.1 pg/mL). She improved with infusion alone. A 31-year-old woman underwent COS with AI and cryopreserved 8 blastocysts. She was hospitalized for OHSS (E2: 429 pg/mL). Her vascular endothelial growth factor (VEGF) levels were high (62 pg/mL) at 8 days after the procedure. She needed hospitalization for 9 days. The planned adjuvant therapy was delayed for a week in both cases. Conclusion: Elevated VEGF levels should be considered as a risk factor of OHSS even if E2 levels are low with AI treatment.